Arabidopsis SMALL DEFENSE-ASSOCIATED PROTEIN 1 Modulates Pathogen Defense and Tolerance to Oxidative Stress - Dutta, Aditya; Choudhary, Pratibha; Gupta-Bouder, Pallavi; Chatterjee, Snigdha; Liu, Po-Pu; Klessig, Daniel F.; Raina, Ramesh (Frontiers in Plant Science, 2020)
Salicylic acid (SA) and reactive oxygen species (ROS) are known to be key modulators of plant defense. However, mechanisms of molecular signal perception and appropriate physiological responses to SA and ROS during biotic or abiotic stress are poorly understood. Here we report characterization of SMALL DEFENSE-ASSOCIATED PROTEIN 1 (SDA1), which modulates defense against bacterial pathogens and tolerance to oxidative stress. sda1 mutants are compromised in defense gene expression, SA accumulation, and defense against bacterial pathogens. External application of SA rescues compromised defense in sda1 mutants. sda1 mutants are also compromised in tolerance to ROS-generating chemicals. Overexpression of SDA1 leads to enhanced resistance against bacterial pathogens and tolerance to oxidative stress. These results suggest that SDA1 regulates plant immunity via the SA-mediated defense pathway and tolerance to oxidative stress. SDA1 encodes a novel small plant-specific protein containing a highly conserved seven amino acid (S/G)WA(D/E)QWD domain at the N-terminus that is critical for SDA1 function in pathogen defense and tolerance to oxidative stress. Taken together, our studies suggest that SDA1 plays a critical role in modulating both biotic and abiotic stresses in Arabidopsis (Arabidopsis thaliana) and appears to be a plant-specific stress responsive protein.